Interferon alpha-induced reduction in the values of myeloid-derived suppressor cells in melanoma patients - Stanojević, Ivan; Gačević, Milomir; Jović, Milena; Mijušković, Željko; Zečević, Radoš; Zolotarevski, Lidija; Jauković, Ljiljana; Rajović, Milica; Novaković, Marijan; Miller, Karolina; Binić, Ivana; Vojvodić, Danilo (Vojnosanitetski pregled, 2015)
Background/Aim. Interaction between tumor cells and host’s immunoregulatory cells in creation of microenvironment that supports tumor progression is the focus of numerous investigations in recent years. Myeloid-derived suppressor cells (MDSCs) are heterogeneous population of immature dendritic cells, macrophages and granulocytes. In cancer patients, these cells accumulate in tumor microenvironment, tumor-draining lymph nodes, peripheral blood and the liver and their numbers correlate with the stage of the disease and the metastatic disease. The aim of the study was to investigate the effect of interferon alpha on MDSCs percentage in peripheral blood of melanoma patients. Methods. The interferon treated melanoma patients were given subcutaneously interferon alpha, in optimal dose, for a period of at least 6 months before the analysis. Blood samples were collected from the melanoma patients (n = 91) and the age/sex matched healthy controls (n = 8). The following anti-human monoclonal antibodies were used for immunostaining: anti-CD15-FITC, anti-CD33-PE, anti-CD45-ECD, anti-HLA-DR PE/Cy5, anti-CD14-FITC, anti-CD16-PE and anti-CD11b-PE. Results. Comparison of myeloid-derived suppressor cells values in the stage 2 melanoma patients with and without interferon alpha therapy did not show a significant difference. When we compared the MDSCs values in the patients within stage 3 melanoma, we found a significant difference in granulocytic subset values between the interferon alpha-treated and the untreated group. Comparison of values of all suppressor cells populations between the interferon alpha-treated patients and healthy controls showed a significant increase in suppressor cells percentage in the melanoma patients. The granulocytic and total MDSCs values were significantly lower in the interferon alpha treated melanoma patients with progression in comparison with untreated patients with stable disease. Conclusion. We confirmed that interferon alpha effect in stage 3 melanoma patients was reduction in MDSCs percentage. We also found an unexpected bounce back of these suppressor cells levels, many months after the discontinuation of interferon alpha therapy.